2017
DOI: 10.1039/c7qm00304h
|View full text |Cite
|
Sign up to set email alerts
|

Light/temperature-enhanced emission characteristics of malononitrile-containing hexaphenyl-1,3-butadiene derivatives: the hotter, the brighter

Abstract: The HPB-CN-coated filter paper exhibited stronger PL intensity as exposure time under UV light prolonged and heating temperature increased, to realize the hotter, the brighter.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
6
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
3
1
1

Relationship

1
4

Authors

Journals

citations
Cited by 12 publications
(6 citation statements)
references
References 23 publications
0
6
0
Order By: Relevance
“…As mentioned above, MPBsc an be cyclized under UV irradiation, and thus, al ight/temperature-enhanced emission based fluorescence" turn-on" probe was preparedb yu sing this unique property. [88] The PL intensity of the HPB-5c-coated filter paper becames tronger as the temperature gradually increased (Figure 10 A), andt he emission maximum was blueshifted as well. The mechanismw as revealed to be that UV light irradiation causes HPB-5c on the filter paper to undergo thermoinduced crystallization, as illustrated in Figure 10 B, which then induces the cyclization of the well-arrangedH PB-5c molecules.…”
Section: Temperaturementioning
confidence: 96%
See 3 more Smart Citations
“…As mentioned above, MPBsc an be cyclized under UV irradiation, and thus, al ight/temperature-enhanced emission based fluorescence" turn-on" probe was preparedb yu sing this unique property. [88] The PL intensity of the HPB-5c-coated filter paper becames tronger as the temperature gradually increased (Figure 10 A), andt he emission maximum was blueshifted as well. The mechanismw as revealed to be that UV light irradiation causes HPB-5c on the filter paper to undergo thermoinduced crystallization, as illustrated in Figure 10 B, which then induces the cyclization of the well-arrangedH PB-5c molecules.…”
Section: Temperaturementioning
confidence: 96%
“…[89] It was shown that the TPB-5c probe has high selectivity for g-globulins over other components in the blood The crystallizationo fH PB-5c on the filter paper and photocyclization of HPB-5cunder UV irradiation uponheating. [88] serum, including serum albumins, fibrinogen, glucose, urea, and cholesterol, as shown in Figure 11.I nf act, these species can barely interferew ith the molecular interactions between TPB-5c and g-globulins. The high specificity of TPB-5c probe enabledi ns itu quantitative detection of g-globulins without isolating g-globulins from the bloods erum.…”
Section: Biological Probesmentioning
confidence: 99%
See 2 more Smart Citations
“…[71][72][73][74][75][76][77][78] Some photo-responsive fluorescent materials with AIE properties based on photocyclization reactions have been reported, and show excellent performance in advanced nanotechnological, biomedical, and photo-physicochemical applications. [79][80][81][82][83][84][85][86][87][88] In a recent example, by introducing rigid spiro scaffolds into diphenylethene moieties, Tang et al synthesized a kind of novel AIEgens (SIPs) with deep-blue emission, which exhibited state-dependent photocyclization behaviors and fluorescence properties. [82] The photocyclization processes and AIE properties are shown in Figure 3A.…”
Section: Photocyclizationmentioning
confidence: 99%